FRI0439 The promising role of lung mri in detecting systemic sclerosis (SSC)-related interstitial lung disease (ILD). (12th June 2018) - Gargani, L.; Bruni, C.; De Marchi, D.; Romei, C.; Guiducci, S.; Bellando-Randone, S.; Aquaro, G.D.; Pepe, A.; Falaschi, F.; Pingitore, A.; Matucci-Cerinic, M.
Abstract : Background: Interstitial lung disease (ILD) is very frequent and highly disabling in patients with systemic sclerosis (SSc). Magnetic resonance imaging (MRI) is not routinely used for the evaluation of the lung, since MRI generally provides a less detailed view of the pulmonary parenchyma, as well as poorer spatial resolution, compared to the non-invasive gold-standard of high resolution computed tomography (HRCT). Thus, its usefulness in the evaluation of interstitial lung disease (ILD) is limited at present. Objectives: To evaluate MRI signals in different pathological and non-pathological lung areas, and to establish their clinical and instrumental correlations. Methods: Thirty-two SSc patients underwent a cardiac MRI with dedicated lung scanning and chest HRCT on the same day. One-hundred-thirty-five regions of interest (ROIs) were identified, and STIR and T1 sequences were acquired[before (T0) and after 5 (T5), 10 (T10) and 15 (T15) minutes from gadolinium injection]. The ROIs were classified according to HRCT as normal, dependent areas (probably related to blood pooling in supine position) and pathological areas(ground glass ±reticulation on HRCT). Mean STIR and T1 times were also calculated for each patients, and correlated with FVC, DLco, B-lines on lung ultrasound and HRCT semi-quantitative scoring (Scleroderma Lung Study score). Patients were followed-up and lung worsening was defined on the basis of clinical judgement and at least >15% DLco decline. Results: Mean STIR and mean T1 times were significantly different between normal, dependent and pathologic areas (p<0.001 between groups). Patients' mean STIR showed a significant correlation with DLco (R=−0.56, p<0.01), HRCT Scleroderma Lung Study score (R=0.52, p<0.01) and B-lines on lung ultrasound (R=0.63, p<0.01). The mean STIR of the 10 patients who developed a worsening pulmonary involvement had significantly different MRI signal intensity in comparison to the 25 patients without worsening pulmonary involvement (125±46 vs 66±37 msec, p<0.01). Conclusions: Our data highlight the usefulness of lung MRI in SSc patients to differentiate normal, dependent and pathologic areas, without need for contrast medium administration, and with good correspondence to other functional and imaging parameters. STIR values may have prognostic implications to predict lung worsening. Lung MRI, although still very preliminary, is a promising imaging tool that in the future may integrate HRCT in SSc-related ILD. Disclosure of Interest: None declared